Continuity, innovations and differences. The concept of the town in the Northern and Southern Netherlands around 1600 (Bulletin KNOB, 1999)
During the reign of Archdukes Albrecht and Isabella in the Southern Netherlands an ever-growing split between the two parts of the Netherlands is evident, especially in the field of politics and religion. A central question emerging here is related to the way in which image and structure of the town developed. To what extent did the Counter Reformation in the south and Calvinism in the north affect urban development?The fascinating aspect of this confrontation is also to be found in the fact that around 1600 geometrical concepts of town planning and the visual perspective were introduced in the architecture of both parts of the Netherlands on a large scale.In the period 1580-1630 Antwerp and Amsterdam played a special role in this respect: Antwerp as a test case for applying concepts such as 'commodity', 'jewel' and 'profit' in the layout of new streets and squares, Amsterdam rather for the eventual realization of the so-called 'canal town'.The writings and drawings of Hans Vredeman de Vries give interesting information on the image of the town. They provide representations according to the method of the central perspective, in a conveniently arranged manner depicting the ideal townscape around 1600.This ideal town is regular and harmonious as far as front elevations of buildings are concerned. They show a preference for arched galleries on the ground floor in order to maximize the public domain at street level and the town structure preferably complies with the grid pattern.Such efforts to achieve unity in floor plan and elevation are intensified by attempts of the authorities to effect codification of the norms adopted in customary law applicable at that time. The publication of the 'Rechten ende Costumen van Antwerpen' (Rights and Customs of Antwerp) in 1582 during the anti-Spanish rule plays a pioneering role here and is frequently imitated in both the Northern and the Southern Netherlands in the following years.Finally, there is the problem of the specific influence of Calvinism versus Counter Reformation on the concept of the new town. In this respect the examples of Coevorden and Scherpenheuvel are to be considered important, because despite their morphological similarities they nevertheless show essential points of difference in the field of the development of meaning of the town. In the case of Coevorden a series of pragmatically and military starting points play a decisive role in the working out of the town concept. However, Scherpenheuvel presents a unique example of the combination of symbolism, religion, town planning, architecture and fortress building in the formation of concepts and realization of the town.